KAJIAN USAHATANI STROBERI DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Mikhael B. Wuner; Lyndon R.J. Pangemanan; Theodora M. Katiandagho; Eyverson Ruauw (COCOS, 2015)
ABSTRACT Rurukan region as the plateau region is an a potensial area for development potensional strawberry farm, which not only can be a life strut farmers, but also can be a potensional region for main development of Strawberries comodities. The purpose of this study is to determine how the process of strawberry farm by the farmers since the cultivation stage to the marketing of products, as well as to determine the level of income from farming strawberries in Tomohon sub district Rurukan East Village, this study lasted for 3 months and the data collected in the form of primary data taken directly from farmer groups of kina, Rurukan. The results showed that the income derived from farming strawberries in one season or eight times harvest for 1000 is Rp.20.887.043 strawberry plants with a total production cost incurred for the 1000 crop of strawberries for Rp.5.377.957 and total receipts amounted to Rp.26.265 000. Revenue Cost Ratio Analysis showed that the strawberry farm in the village Rurukan obtain the value of R / C of 4.92. it means that every 1 rupiah costs strawberry farmers can result in revenue of 4.92. this shows that strawberry farm in the Rurukan Village is profitable.